Formation of Ukraine’s Climate Policy in the Context of European Integration - Golovko, Liudmyla; Yara, Olena; Uliutina, Olena; Tereshchenko, Andrii; Kudin, Andrew (European Journal of Sustainable Development, 2021)
It is an indisputable fact that one of the most important problems today is global climate change. Climate change affects everyone and requires a concerted effort at regional, national and international levels. The most intensive legal regulation of environmental protection, including climate change, which has an extremely negative impact on the environment, is carried out on the European continent. The European Union is a leader in climate change prevention and an example for other countries. The state policy of Ukraine on legislative adaptation is formed as an integral part of legal reform in Ukraine and is aimed at ensuring common approaches to rule-making, mandatory consideration of European Union legislation in rule-making, training of qualified specialists, creating appropriate conditions for institutional, scientific, educational, technical, financial support of the process of adaptation of the legislation of Ukraine. In the scholarly work global and European trends in climate change prevention policy were revealed. The adaptation of Ukrainian legislation in the field of climate change to EU law was analyzed. The conceptual foundations of the environmental policy of Ukraine in the context of climate change were considered. The challenges and problems on the way to the implementation of climate policy were determined.